2019
DOI: 10.1093/cz/zoz045
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, genetics, and the partial life cycle of Oncomegas wageneri in the Gulf of Mexico

Abstract: Despite the diversity and ecological importance of cestodes, there is a paucity of studies on their life stages (i.e., complete lists of intermediate, paratenic, and definitive hosts) and genetic variation. For example, in the Gulf of Mexico (GoM) 98 species of cestodes have been reported to date; however, data on their intraspecific genetic variation and population genetic studies are lacking. The trypanorhynch cestode, Oncomegas wageneri, is found (among other places) off the American Western Atlantic Coast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…The barcoding sequence data generated for Serrasentis gibsoni n. sp. individuals from eight different oceanic sites in the GoM revealed extremely high intraspecific genetic variation (0.0057 nucleotide diversity) Martínez-Aquino et al (2020). recently detected high intraspecific genetic variation with similar values (0.0086 nucleotide diversity), using the same molecular marker for the trypanorhynch cestode, Oncomegas wageneri (Linton, 1890) Dollfus, 1929, from C. chittendeni from the GoM.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…The barcoding sequence data generated for Serrasentis gibsoni n. sp. individuals from eight different oceanic sites in the GoM revealed extremely high intraspecific genetic variation (0.0057 nucleotide diversity) Martínez-Aquino et al (2020). recently detected high intraspecific genetic variation with similar values (0.0086 nucleotide diversity), using the same molecular marker for the trypanorhynch cestode, Oncomegas wageneri (Linton, 1890) Dollfus, 1929, from C. chittendeni from the GoM.…”
mentioning
confidence: 71%
“…takes place in demersal and/or reef-associated habitats. Future studies of acanthocephalans from the GoM following a study program as suggested by Blasco-Costa & Poulin (2017) to elucidate parasite life cycles (i.e., approaches based on morphological matching and/or genetic matching [e.g., Martínez-Aquino et al 2017, 2020]), can provide a foundation to develop a taxonomical diagnosis of each specific phase of the species of acanthocephalans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El cestodo O. wageneri ya ha sido registrado en otros elasmobranquios para la misma zona de estudio (Méndez & Dorantes-González, 2017;Méndez et al, 2018;Martínez-Aquino et al, 2019). Vidal-Martínez et al (2014) (Fusco & Overstreet, 1978) Cárdenas & Lanfredi, 2005 es conocido por infectar peces de la familia Scaridae, la cual está incluida en la dieta de la raya látigo.…”
Section: O S C E S T O D O S a C A N T H O B O T H R I U M S P 1 Yunclassified
“…Oncomegas wageneri is a larval cestode infecting flatfishes collected from oil extraction zones of the Mexican Gulf of Mexico (Vidal-Martínez et al 2014;Centeno-Chalé et al 2015;Vidal-Martínez et al 2015;Martínez-Aquino et al 2019). This parasite is a good candidate for the detection of PAH metabolites because it has a wide geographical distribution in the Gulf of Mexico, has a high prevalence and mean abundance in its host, and inhabits the intestine of the flatfishes where it can be exposed to whatever the host is ingesting (including food contaminated with PAH) (Vidal-Martínez et al 2014).…”
Section: Introductionmentioning
confidence: 99%